The Effectiveness of the 5E Learning Cycle Model in Students’ Mathematics Engagement Learning - Ghunaimat, Mohammad; Alawneh, Esraa (International Journal of Mathematics and Mathematics Education (IJMME), 2025)
Purpose – The goal of this research is to find out how well the 5E Learning Cycle Model works to increase students' interest in studying mathematics. The study specifically seeks to ascertain whether using this paradigm, as opposed to more conventional teaching techniques, results in statistically significant gains in students' behavioral, emotional, and cognitive involvement. Methodology – This study looked at how the 5E Learning Cycle Model affected students' interest in learning mathematics using a quasi-experimental approach with a non-equivalent control group. The approach made it possible to compare a control group that was taught using traditional techniques with an experimental group that received the intervention. Findings – The study's findings showed that students' engagement with mathematics learning was significantly improved by the 5E Learning Cycle Model. Students in the experimental group showed greater levels of engagement across all examined dimensions—behavioral, emotional, and cognitive—than those in the control group, according to an analysis of the post-intervention data. The observed improvements were not the result of chance, as statistical testing verified that these differences were significant at the 0.05 level. In terms of involvement, interest, and comprehension depth, the experimental group continuously performed better than the control group. Novelty – By adapting the 5E Learning Cycle Model, which is often utilized in scientific instruction, to the field of mathematics learning with a particular focus on student involvement, this study makes a unique contribution to mathematics education. Although the 5E Model is well known for encouraging inquiry and conceptual understanding in scientific classes, little is known about how effective it is in math classes. Significance – The findings of this study have important ramifications for a number of education stakeholders, including students, teacher training institutions, curriculum developers, educational leaders, and policymakers.